Transatlantic restart: Proposals for trade cooperation between the EU and the United States - Gabriel Felbermayr; Vincent Stamern (Stiftung Familienunternehmen, 2021)
The economic impact of punitive US tariffs affect not only the aircraft industry, but also European family businesses: manufacturers of alcoholic beverages (e.g. spirits and wine producers) are the second most severely affected group. Confectionery manufacturers and the toolmaking industry have also suffered. Professor Gabriel Felbermayr, PhD, Head of the Kiel Institute for the World Economy, proposes a tariff agreement or at least the mutual offsetting of punitive tariffs between the United States and EU.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Außenwirtschaftspolitik; Handelskonflikt; EU-Staaten; USA; Internationale Wirtschaftsbeziehungen; Außenwirtschaftspolitik; Handelskonflikt; EU-Staaten; USA